Knowledge, perceptions, and exposure to bats in communities living around bat roosts in Bundibugyo district, Uganda: implications for viral haemorrhagic fever prevention and control - Ninsiima, L.R.; Nyakarahuka, L.; Kisaka, S.; Atuheire, C.G.K.; Mugisha, L.; Odoch, T.; Romano, J.S.; Klein, J.; Mor, Siobhan M.; Kankya, C. (Springer, 2024)
Background Bats are a reservoir for many viruses causing haemorrhagic fevers. Proximity to bats is a risk factor for virus spillover to animals and humans. We conducted this study to assess knowledge, perceptions, and exposure to bats in communities living near bat roosts in Bundibugyo District, Uganda.